Cultivation and Proximate Analysis of Pink Oyster Mushroom (Pleurotus eous) in Doimukh, Arunachal Pradesh (International Journal of Food and Nutritional Sciences, 2022)
Pleurotus eous also known as Pink oyster mushroom is an edible mushroom species and regarded as food because of their high nutritional values with a rich source of dietary fibers, protein and minerals and exclusively low fat contents. The cultivation of Pleurotus eous was carried out during the month of May - June, 2022 at the mushroom hut built in the premises of Botany department, Rajiv Gandhi University, Arunachal Pradesh and the nutrient composition of harvested fruitbodies of Pleurotus eous grown on various substrates such as Paddy straw (PS), Rice Bran (RB), Saccharum spontaneum (SS), PS+SS, PS+RB and SS+RB were determined according to the standard protocol. The nutritional component of all the selected substrates except Rice bran (contaminated) supported the growth of Pleurotus eous. The mushrooms harvested from SS+RB contained the highest moisture (93.65%), ash (10.11%), and crude fibre (28.01%), while the highest protein contents (29.0%) was observed in PS+SS. It has been observed that cultivated mushrooms, Pleurotus eous are abundantly endowed with nutritive constituents, which could be used as source of food and medicine as they are rich in protein and low in fats.